Disiplin Gereja: Sebagai Aplikasi bagi Pertumbuhan Karakter dan Rohani dalam Komunitas Jemaat (Jurnal Pendidikan Agama dan Teologi, 2025)
The church is the Body of Christ that carries out God’s vision and mission in the world to bring many lost souls. Often the church is confused when it has to determine its attitude towards people who sin. One extreme attitude is to just let someone fall into sin because they are afraid of offending that person. Another extreme attitude is to hate sin so much that they also hate the person who does it. Discipline in the church is a major oversight in some churches today. The church also often misunderstands the meaning of church discipline and misimplements it to the congregation. The church misunderstands that church discipline is a form of punishment given not as a warning or reprimand to regret mistakes and return to the right path. From the title of this article, the author describes the results of the discussion using the Qualitative method through a literature research study sourced from scientific papers in the form of journals and related articles that produce several discussions including: the definition and purpose of church discipline, forms of church discipline, challenges in implementing church discipline, and the last is how church discipline can build a spiritually and socially healthy congregation community. The discussion of this article is described by the author to the readers so that they can increase their insight and even teach and encourage the church to always be firm in disciplining congregations who commit sins based on the truth of God’s word.